2021
DOI: 10.14336/ad.2020.0904
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Frailty on Spine Surgery: Systematic Review on 10 years Clinical Studies

Abstract: Frailty is a condition characterized by a high vulnerability to low-power stressor. Frailty increases with age and is associated with higher complications and mortality. Several indexes have been used to quantify frailty. Spine diseases, both degenerative and oncologic, frequently require surgery which is related to complications and mortality. Aim of the present systematic review was to collect the most frequently used frailty indexes in clinics to predict surgical outcomes in patients affected by spine disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 63 publications
1
47
0
Order By: Relevance
“…The prevalence of frailty increases with age, and it is more frequent in females than in males. Numerous indices are currently in use for the assessment of frailty based on a variety of settings and diseases, related to the “Frailty Phenotype” or the “Deficit Accumulation Index or Frailty Index” models [ 8 ]. On one hand, clinical trials have demonstrated that the presence of OA is significantly associated with a higher risk of being frail [ 9 , 10 , 11 , 12 , 13 , 14 ]; on the other hand, the role of frailty in the development of degenerative joint diseases has been hypothesized due to the increase in pro-inflammatory mediators and the presence of sarcopenia associated with a higher fall risk [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of frailty increases with age, and it is more frequent in females than in males. Numerous indices are currently in use for the assessment of frailty based on a variety of settings and diseases, related to the “Frailty Phenotype” or the “Deficit Accumulation Index or Frailty Index” models [ 8 ]. On one hand, clinical trials have demonstrated that the presence of OA is significantly associated with a higher risk of being frail [ 9 , 10 , 11 , 12 , 13 , 14 ]; on the other hand, the role of frailty in the development of degenerative joint diseases has been hypothesized due to the increase in pro-inflammatory mediators and the presence of sarcopenia associated with a higher fall risk [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a previous systematic review by Veronesi et al found that there may be an issue regarding the relationship between the frailty level and gender, with worsening of frailty being prevalent in women, which represents an area of future research with regards to accuracy of frailty assessments. [51] The FI is not intended to replace current validated scoring systems specific to prognostication of spinal metastatic disease, [8,12,52] rather the addition of FI evaluation may improve their predictability performance. Ghori et al improved the predictability of survival from the modified Baur score [52] (AUC=0.64) by the addition of nutrition and ambulation (AUC=0.74), termed the New England Spinal Metastasis Score (NESMS).…”
Section: Discussionmentioning
confidence: 99%
“…The predictive value of frailty scales could be affected by various factors other than age as well. This review revealed the predictive values of frailty scales including mFI-11, the most frequently used scale in the spine population [13], were controversial depending on a variety of study settings (e.g. spinal disorders, surgical procedures, age and frailty at baseline, frailty scales, cut-off values, and outcomes of the study).…”
Section: Different Settings Examined Using Different Frailty Scalesmentioning
confidence: 99%
“…spinal disorders, surgical procedures, age and frailty at baseline, frailty scales, cut-off values, and outcomes of the study). Although Veronesi et al recently concluded that mFI can be applied at any age in all spinal disorders [13], this means, that as yet we have to pay careful attention in deciding which frailty scale to use depending on the outcomes and the setting of interest [115].…”
Section: Different Settings Examined Using Different Frailty Scalesmentioning
confidence: 99%
See 1 more Smart Citation